Preparation method of aluminum ash and molecular sieve co-supported active metal multifunctional catalyst and application of aluminum ash and molecular sieve co-supported active metal multifunctional catalyst in tar cracking

Through aluminum ash and HZSM-5 molecular sieve co-loading of active metal catalysts, the problem of tar is easily blocked during the pyrolysis of biomass hydrogen production is solved, and the production of high-efficiency hydrogen-rich gas is achieved, and the preparation cost and life of the catalyst are reduced.

CN119565662APending Publication Date: 2025-03-07HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411460188.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

There is a problem that tar can easily lead to equipment blockage during the existing biomass pyrolysis process, and the high cost and short life of the catalyst limit the efficiency and quality of hydrogen production.

Method used

Aluminum ash synergistic HZSM-5 molecular sieve is used to co-load active metal multifunctional catalyst. The activated aluminum ash is mechanically mixed with the molecular sieve, and the active metal is loaded with ultrasonic or microwave assisted method to form a Ni-Fe/ASA@HZSM-5 catalyst, which is used for tar cracking to prepare hydrogen-rich gas.

Benefits of technology

It realizes efficient and selective production of hydrogen-rich gas, with a gas yield of ≥70%, and reduces the preparation cost of the catalyst, extends the life of the catalyst, and improves the quality of the synthesis gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565662A_ABST
    Figure CN119565662A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an aluminum ash-molecular sieve co-supported active metal multifunctional catalyst and application of the aluminum ash-molecular sieve co-supported active metal multifunctional catalyst in tar cracking, and the preparation method comprises the following steps: uniformly mixing activated aluminum ash and a molecular sieve to prepare an aluminum ash-molecular sieve co-carrier; active metal and the aluminum ash-molecular sieve co-carrier are added into a dispersing agent, the active metal is loaded on the co-carrier through auxiliary methods such as ultrasonic treatment, and a solid is obtained after redundant dispersing agent is removed; and drying the solid, and calcining in an inert atmosphere to prepare the aluminum ash and molecular sieve co-supported catalyst. According to the invention, the aluminum ash and the HZSM-5 molecular sieve are taken as raw materials of a co-carrier, a multifunctional series Ni-based catalyst (Ni-Fe / ASA-HZSM-5 catalyst) for preparing high-quality hydrogen-rich gas through pyrolysis of biomass and by-products thereof is successfully synthesized, hydrogen-rich gas can be selectively produced, and the highest yield is up to 80%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tar catalytic cracking and thermal reforming, and specifically relates to a preparation method of an aluminum ash-coordinated molecular sieve co-loaded active metal multifunctional catalyst and its application in tar cracking. Background Art

[0002] As an ideal clean energy, hydrogen energy has the advantages of high energy, cleanliness, high efficiency, renewable, sustainable and recyclable, and is considered to be the most ideal green energy carrier in the future. At present, hydrogen energy mainly comes from fossil fuel reforming, gasification and water electrolysis such as coal, natural gas and petroleum by-products; but due to limited resource reserves and high investment costs, as well as excessive global warming caused by the use of fossil fuels, the advantages of green hydrogen from renewable energy are becoming increasingly prominent. As the world's fourth largest energy source, biomass energy has the advantages of being renewable, large reserves, carbon balanced, clean, and having a high hydrogen content and high availability. It has good application prospects in the preparation of green hydrogen and is of great significance to alleviating energy shortages and environmental crises.

[0003] Biomass hydrogen production technology mainly includes thermochemical method and biological method. Thermochemical method refers to converting biomass into hydrogen-rich fuel gas through thermochemical treatment and obtaining pure hydrogen through separation; it mainly includes steam gasification hydrogen production, supercritical water gasification hydrogen production and biomass pyrolysis / reforming hydrogen production. Among them, pyrolysis / reforming method has become an effective and attractive method due to its advantages such as low pollutant emissions and high hydrogen production efficiency. However, in this process, since the products of biomass pyrolysis hydrogen production contain tar, the equipment is prone to blockage and other problems. In addition, the presence of oxygen-containing compounds such as acids, alcohols, phenols, and ketones will reduce the quality of biofuels. The selection of a suitable catalyst can not only effectively reduce the reaction temperature and increase the reaction rate, but also selectively increase the yield of the target product, thereby achieving directional regulation of the product.

[0004] In the past few decades, people have conducted extensive research on the production of hydrogen-rich gas by catalytic pyrolysis of biomass. Many studies have found that metal loading can effectively improve tar conversion and inhibit carbon deposition, especially Ni-based catalysts can effectively inhibit carbon deposition during the reforming process; Lang et al. used iron-based aluminum ash catalyzed pyrolysis of wood waste to produce hydrogen, which increased the hydrogen content by 18.48%. Kaltume et al. found that the hydrogen content in the synthesis gas was significantly increased after adding steam and catalyst when studying pyrolysis-catalytic steam reforming of different biomasses. Therefore, by designing and synthesizing new high-activity and high-stability catalysts, carbon deposition in the reforming process can be effectively eliminated, the quality of synthesis gas can be improved, and the hydrogen yield can be increased; Ye et al. prepared Ni / MCM-41 catalysts with and without carrier acidity (Al, Si, Na) and used them to catalyze biomass gasification to produce hydrogen. The results showed that the addition of Al enhanced the reducing ability of NiO nanoparticles and converted chemical substances into small molecular products including H2 and CO through cracking, thereby increasing the hydrogen yield; Williams et al. investigated the catalytic performance of nickel-based catalysts with different carriers (Al2O3, MgO, CeO2, ZSM-5) for polypropylene cracking and gasification to produce hydrogen. The results showed that Al and Mg-Al-supported nickel-based catalysts have good catalytic abilities in generating hydrogen and preventing coking; however, it is well known that the high catalytic activity, thermal stability and long life of this type of catalyst depend on suitable carriers, and the carrier plays a mechanical supporting role on the active components and chemical reactions can occur between the carrier and the active components, resulting in the formation of new species with catalytic properties. Therefore, the role of the carrier is reflected in reducing the cost of the catalyst, improving the mechanical strength of the catalyst, extending the life of the catalyst, changing the direction and selectivity of the reaction, etc. Many researchers are committed to exploring the potential of various metal oxides or porous materials as catalyst carriers to change their structure and properties.

[0005] Aluminum ash, as waste, residue or residue from raw material processing in the aluminum smelting industry, can be divided into white, black and salt cake, depending on the amount of aluminum present and the form of the waste. However, the negative accumulation of aluminum ash not only occupies a large amount of land, but also its strong alkalinity will cause serious pollution to the soil, air and groundwater. The main components of typical aluminum ash are metallic aluminum, aluminum oxide, aluminum chloride and transition metal oxides, among which aluminum oxide accounts for 10-80% and contains a large amount of heavy metal oxides such as Na2O, CaO, MgO, Fe2O3, which is consistent with Al2O3 being the most commonly used supported catalyst carrier; at the same time, alkali metals and transition metals such as Ca, Fe, Mg are functional catalysts for reactions such as biomass pyrolysis, gas reforming, and carbon deposition gasification. In particular, Fe not only has acceptable reactivity and catalytic tar decomposition for H2 and CO, but also has certain carbon removal and carbon resistance capabilities and has a significant promoting effect on tar conversion and water-gas shift reaction; heavy metals such as Cu and Zn have extremely strong catalytic effects on tar decomposition and carbonization, and oxides such as Na, Mg, Fe, and K are important catalysts for hydrogen production reactions. Preliminary studies have found that aluminum ash can significantly improve its internal structure after pretreatment, and can replace some commercial Al2O3 for catalysts or carriers, abrasives, cutting tools, advanced ceramics, etc., with high recycling value. Summary of the invention

[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a multifunctional catalyst of aluminum ash and HZSM-5 molecular sieve co-loaded with active metals.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a multifunctional catalyst of aluminum ash and HZSM-5 molecular sieve co-loaded with active metals, comprising:

[0010] The activated aluminum ash and the molecular sieve are mechanically mixed uniformly to obtain an aluminum ash-molecular sieve co-carrier;

[0011] After mixing the active metal precursor and the co-carrier, a dispersant is added to load the active metal on the co-carrier, and a solid is obtained after removing excess dispersant;

[0012] The obtained solid is calcined in an inert atmosphere to obtain an aluminum ash-molecular sieve co-supported active metal catalyst;

[0013] Wherein, the active metal precursor includes one or more of nickel nitrate, iron nitrate, magnesium nitrate, cerium nitrate, calcium nitrate, and cobalt nitrate;

[0014] The dispersant includes deionized water and ethanol;

[0015] The mass percentage of the active metal relative to the co-carrier is 1 to 8 wt.%;

[0016] The activated aluminum ash accounts for 20% to 80% of the mass of the molecular sieve.

[0017] As a preferred embodiment of the preparation method of the present invention, the preparation method of the activated aluminum ash includes hydrothermal activation and acid activation;

[0018] Wherein, the hydrothermal activation temperature is 140-200°C, and the activation time is 2-4h;

[0019] Wherein, the acid-activated preparation method comprises:

[0020] After the aluminum ash slag is passed through a 80-100 mesh sieve, it is calcined at 600-800°C for 2-3 hours to obtain calcined aluminum ash;

[0021] The calcined aluminum ash is added into the acid solution, stirred evenly, ultrasonically impregnated, centrifuged, the supernatant is poured out, the acidified aluminum slag is placed in a muffle furnace for high temperature roasting at 600°C for 3 hours, and taken out after natural cooling to obtain acid-activated aluminum ash.

[0022] As a preferred embodiment of the preparation method of the present invention, the acid solution comprises sulfuric acid, acetic acid and phosphoric acid, and the acid concentration is 1 to 7 mol / L.

[0023] As a preferred embodiment of the preparation method of the present invention, the preparation method of the molecular sieve comprises:

[0024] The molecular sieve raw material was ground and passed through an 80-mesh sieve, placed in a muffle furnace and heated to 550°C at a heating rate of 20°C / min, and calcined for 3 h;

[0025] The molecular sieve raw material includes HZSM-5 zeolite molecular sieve.

[0026] As a preferred embodiment of the preparation method of the present invention, the active metal is loaded on a common carrier, and the loading method includes ultrasonic-assisted method, microwave-assisted method and ion exchange method.

[0027] As a preferred embodiment of the preparation method of the present invention, the ultrasonic assisted method comprises the following steps: the ultrasonic treatment power is 60 to 80 W, and the treatment time is 20 to 30 min.

[0028] As a preferred embodiment of the preparation method of the present invention, the solid is obtained after removing the excess dispersant, wherein the removal method includes drying method and natural volatilization method.

[0029] As a preferred embodiment of the preparation method of the present invention, the calcination is carried out in an inert atmosphere, wherein the calcination temperature is 500-600° C. and the calcination time is 3-4 hours.

[0030] As a preferred scheme of the preparation method described in the present invention, the aluminum ash and molecular sieve co-load an active metal catalyst, wherein the active metal includes metal Fe and metal Ni, the mass percentage of metal Fe relative to the co-carrier is 1 to 4 wt.%, and the mass percentage of metal Ni relative to the co-carrier is 4 to 8 wt.%.

[0031] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of aluminum ash and molecular sieve co-loaded nickel-iron catalyst in catalytic tar cracking to prepare hydrogen-rich fuel gas.

[0032] Beneficial effects of the present invention:

[0033] (1) In view of the shortcomings of the heavy components of high-temperature pyrolysis gas, such as easy coking and difficulty in utilization, low performance of traditional molecular sieves, and difficulty in resource utilization of aluminum ash, the present invention uses transition metal Ni as an active component, aluminum ash replaces HZSM-5 molecular sieve and forms a synergistic effect between carriers to obtain a raw material for cheap production of hydrogen-rich gas using aluminum ash and HZSM-5 molecular sieve materials as co-carriers. A new approach and method for the pyrolysis of biomass and its by-product tar to produce high-quality hydrogen-rich gas is successfully synthesized, which can selectively produce hydrogen-rich gas. The mechanism of pyrolysis of aromatic tar model components on this type of catalyst to produce hydrogen-rich gas is revealed, and the yield of hydrogen-rich gas is ≥70%.

[0034] (2) The Ni-Fe / ASA@HZSM-5 catalyst of the present invention, when ASA replaces 60% of the HZSM-5 molecular sieve, in a secondary fixed bed reactor, at a pyrolysis temperature of 600°C / catalytic reforming temperature of 800°C, with nitrogen as a carrier gas, the yield of gases (H2, CH4, CO and CO2) produced by the pyrolysis of toluene, a single model compound of tar, is 113.95 mL / g toluene, and the proportions of H2, CH4 and CO account for 35.68%, 55.73%, 4.46% and 4.12% of the total gas yield, respectively, showing good catalytic activity; it was found that the Ni-Fe catalyst co-loaded with ASA and HZSM-5 molecular sieve is one of the effective catalysts for producing hydrogen-rich gas.

[0035] (3) The Ni-Fe / ASA@HZSM-5 catalyst prepared by using ASA as a co-carrier to replace part of the HZSM-5 molecular sieve has good catalytic activity and stability, realizes the recycling of industrial solid waste in the field of biomass resources, reduces the preparation cost of the catalyst, and provides a new idea for the preparation of catalysts used to catalyze the pyrolysis of biomass tar to prepare hydrogen-rich gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0037] Figure 1 This is a graph showing the effect of the amount of ASA added on the catalytic toluene pyrolysis performance in an embodiment of the present invention.

[0038] Figure 2 It is the XRD spectrum of Ni-Fe / ASA@HZSM-5 series catalysts in the embodiments of the present invention.

[0039] Figure 3 This is a graph showing the effect of the number of cycles of catalytic toluene pyrolysis of Ni-Fe / ASA@HZSM-5 catalyst on the catalytic activity in an embodiment of the present invention.

[0040] Figure 4 This is a graph showing the effect of the amount of catalyst on the thermal decomposition performance of toluene in an embodiment of the present invention.

[0041] Figure 5 These are SEM images of the catalyst after toluene pyrolysis reaction at different pyrolysis temperatures in the embodiments of the present invention.

[0042] Figure 6 Schematic diagram of a secondary fixed bed in an embodiment of the present invention. DETAILED DESCRIPTION

[0043] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0044] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0045] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0046] In the embodiment of the present invention, HZSM-5 (Si:Al=25) zeolite molecular sieve and aluminum dross (AD) are used as co-carriers. In order to improve their mechanical strength and remove impurities therein, the HZSM-5 molecular sieve is ground and passed through an 80-mesh sieve, placed in a muffle furnace and heated to 550°C at a heating rate of 20°C / min, calcined for 3h, and set aside; AD is passed through an 80-mesh sieve and placed in a muffle furnace and calcined at 600°C for 3h, and stored for use, which is called calcined aluminum dross (CAD), and its specific properties are shown in Table 1.

[0047] Table 1

[0048]

[0049]

[0050] Nickel nitrate hexahydrate (Ni(NO3)2·6H2O, AR) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O, AR) were used as precursors of active component metallic nickel and auxiliary iron, respectively, and toluene (C7H8, AR) was used as a tar model component.

[0051] In the present invention, the gas products obtained by pyrolysis are quantitatively analyzed by gas chromatograph (GC);

[0052] The gas release rate is calculated by the nitrogen balance method shown in formula (1). The gas yield is calculated based on the gas release rate and the amount of tar model compound toluene, see formulas (2) and (3).

[0053]

[0054] Y i =γ i ×m b (2)

[0055] M i =Y i ×ρ i (3)

[0056] (1) where γi is the release rate of gas i, ml / min; v i is the volume percentage of i gas in the tail gas of the fixed bed reactor measured by GC, %; v N2 is the volume percentage of N2 in the tail gas of the fixed bed reactor determined by GC, %;

[0057] (2) In the formula, m b is the mass of toluene, the tar model compound involved in the pyrolysis reaction, g; Y i is the total yield of gas i, ml / min·g; (3) where M i is the mass flow rate of component i, g; is the density of component i at 100°C, g / cm 3 .

[0058] Determination of liquid product in the present invention:

[0059] The pyrolysis oil after pyrolysis of biomass tar was dissolved in 10 ml of dichloromethane and tested by gas chromatography (GC)-mass spectrometry (MS) under electron impact ionization mode.

[0060] Specific test conditions: 1uL of pyrolysis tar was injected by automatic syringe split injection, the voltage was 70eV, the split ratio was 20:1, the ion source temperature was 250℃, and the furnace temperature program was: initial column temperature 40℃, kept warm for 2min, then heated to 280℃ at a rate of 10℃ / min, kept warm for 5min, and the total running time was about 29min; the carrier gas was ultrapure He (>99.999%), and the flow rate was 1.0ml / min.

[0061] The chemical workstation NIST14 (National Institute of Standards and Technology) standard spectral library and area normalization method were used to qualitatively and quantitatively analyze the components. The analysis of tar was repeated more than three times, and the relevant yields were calculated based on the three-phase products.

[0062] Example 1

[0063] (1) Preparation of acid activated aluminum ash:

[0064] The composition of aluminum ash activated by 3 mol / L H2SO4 is shown in Table 2.

[0065] Table 2

[0066]

[0067] (2) Taking the amount of ASA (set to 0%, 20%, 40%, 60%, 80%, and 100% relative to the mass of HZSM-5 molecular sieve) as the influencing factor, a series of Ni-Fe / ASA@HZSM-5 catalysts were prepared by ultrasonic-assisted impregnation method;

[0068] Using deionized water as a dispersant, nickel nitrate hexahydrate, iron nitrate nonahydrate and aluminum ash-molecular sieve co-carrier are added, active metals Fe and Ni are loaded on the co-carrier by ultrasonic treatment, and water is evaporated to obtain a solid;

[0069] After the solid is dried, it is calcined in an inert atmosphere to obtain an aluminum ash-co-molecular sieve co-supported nickel-iron catalyst;

[0070] Among them, the nominal amount of Ni was set to 8wt.%, and the nominal amount of Fe was 4wt.%. In order to ensure the uniformity of metal loading, ultrasound was used to assist the solution impregnation at an ultrasonic power of 80W for 20min; then, the stirred solution was gradually heated to 80°C until the water was completely evaporated; then the viscous sample was placed at 105°C to dry for 12h; finally, in an inert atmosphere, the catalyst containing metal species was calcined in a tubular furnace at 550°C for 3h.

[0071] (3) The reaction is carried out in a two-stage fixed bed consisting of a pyrolysis section (100), a catalytic reforming section (200), a liquid condensation section (300) and a gas collection section (400), see Figure 6 ;

[0072] Specifically, the pyrolysis section (100) includes a model material injection device (101) and a pyrolysis generation device (102);

[0073] The catalytic reforming section (200) comprises a cabinet (201), a heating furnace (202), a thermocouple (203), a catalyst (204), a temperature control box (205), a nitrogen bottle (206), a pressure gauge (207), and a gas flow meter (208);

[0074] The liquid condensation section (300) comprises a condensation device (301) and a collecting bottle (302);

[0075] The gas collection section (400) includes a U-shaped dryer (401) and a gas collection bag (402).

[0076] With nitrogen as the carrier, the temperature of the pyrolysis section is 600°C, and the catalytic reforming temperature is 800°C. When the amount of catalyst is set to 5g and placed in the catalytic reforming section, toluene is introduced at a rate of 1ml / min through a peristaltic pump for catalytic cracking. The change rules of toluene conversion rate and product yield are as follows: Figure 1 .

[0077] Depend on Figure 1 It can be seen that when 60% ASA is added, the yields of gas, liquid and solid of toluene cracking catalyzed by HZSM-5 supported Ni-Fe catalyst (Ni-Fe / HZSM-5) are 63.37%, 28.13% and 8.50% respectively, and the toluene conversion rate is 88.38%; the gas yield is 118.63mL / g, indicating that Ni-Fe / HZSM-5 is an effective catalyst for the production of hydrogen-rich gas and provides abundant active sites for the thermal decomposition of toluene.

[0078] With the addition of ASA, the gas and liquid conversion rates increased to 67.75% and 32.06% respectively, and the solid conversion rate decreased significantly to 0.20%. This indicates that the addition of ASA and HZSM-5 formed a complementary effect between the carriers, which promoted the decomposition and removal of the side chains of toluene and provided an oxygen source for the reaction system. It also formed a CO non-polar skeleton with the functional groups of aromatic hydrocarbons and alkane derivatives, thereby promoting the toluene cracking and gasification reactions and carbon deposition gasification reactions. It is an effective catalyst for the directional hydrogen production from toluene cracking.

[0079] As the amount of ASA added increased from 20% to 60%, the gas conversion rate increased to the maximum (70.78%), and the liquid and solid conversion rates decreased to the minimum; accordingly, the gas yield reached the maximum (113.95 mL / g -toluene ); It shows that the appropriate amount of ASA and HZSM-5 co-loaded Ni-Fe catalyzed toluene pyrolysis promoted the source pyrolysis of toluene and improved the quality of the gas product.

[0080] Compared with Ni-Fe / HZSM-5 catalyst, ASA can be used as a heat carrier for the distribution of various products during toluene pyrolysis, and synergistically with HZSM-5 to enhance the ability of Ni-Fe / HZSM-5 to improve carbon deposit gasification and tar reforming gas production; in particular, high-content gas can be obtained by adjusting the appropriate amount of ASA; at the same time, the presence of auxiliary iron enhances the dispersion of nickel species, providing a guarantee for improving pyrolysis efficiency and reducing the amount of heavy hydrocarbons in the polymerization process, and forms a tight and stable Al-Fe inorganic structural framework with Al in the carrier, creating conditions for the synergistic effect of the solid heat carrier.

[0081] When the amount of ASA continued to increase to 100%, the gas conversion rate decreased by 6.29%, among which the yields of H2, CH4, CO, and CO2 decreased by 23.99%, 9.70%, 3.89%, and 3.82%, respectively; aluminum ash as a co-carrier is the micronization of the active component, which will increase the active surface area of ​​the catalyst and form a strong synergistic effect of metal-carrier, making the properties of the overall catalyst better than those of the active component and the carrier; however, too much ASA will lead to poor dispersion of the co-carrier, and poor synergistic effect will lead to low dispersion of the active component, affecting the distribution of active sites on the surface of the solid heat carrier, resulting in insufficient thermal decomposition of toluene or too little time to crack and condense to form liquid or form carbon deposits; thereby increasing the liquid and solid conversion rates to 34.81% and 0.70%, respectively, reducing the ability of tar cracking to produce hydrogen.

[0082] (4) XRD analysis was further performed on the Ni-Fe / ASA@HZ-5 series catalysts prepared with different ASA amounts (0%, 20%, 40%, 60%, 80%, and 100% relative to the mass of the HZSM-5 molecular sieve). The results are shown in Figure 2. Figure 2 .

[0083] Depend on Figure 2 (a) It can be seen that after adding ASA, the Ni-Fe / 20%ASA@HZSM-5 catalyst has an overlap of Al2O3 and SiO2 between 0-10° and 23-29°, which also contains overlapping peaks of oxides corresponding to elements such as K, Na, Mg, and Ca, which are mainly provided by ASA; this shows that ASA and HZSM-5 have good dispersibility during the ultrasonic-assisted impregnation process and can be used as co-carriers for the loading of active components.

[0084] and Figure 2 (b) Compared with the catalysts prepared by replacing HZSM-5 with different amounts of ASA, the catalysts not only showed a similar crystal structure to the Ni-Fe / HZSM-5 catalyst, but also a large amount of Fe-Ni alloy structure, with peaks at 2θ of 20.36°, 29.88°, 31.36°, 37.12°, 45.38°, and 49.5°; and the amount of Ni-Fe alloy structure also increased, located at 2θ of 29.18° and 49.50°, respectively. In addition, overlapping peaks of Ni-Fe-Al trimetallic were found at 2θ of 23.02°, 49.44°, and 45°, indicating that the Ni-Fe / ASA@HZSM-5 series catalysts have comparable catalytic activity and stability to the Ni-Fe / HZSM-5 catalyst.

[0085] As the amount of ASA increases, the above peaks gradually become more obvious, especially when the amount of ASA is 60% and the amount of HZSM-5 is 40%, the XRD diffraction peaks of the Ni-Fe / 60%ASA@HZ-5 catalyst have fewer impurities and neat peaks, and the peaks of the Fe-Ni alloy structure are clearer. When the amount of ASA continues to increase to 80% and 100%, the peak area between 23.06-24.36° gradually decreases, indicating that the overlapping peaks of the Ni-Fe-Al trimetallic and the peaks of the Fe-Ni alloy structure gradually become blurred and the peak time is significantly delayed; indicating that the synergistic effect between the carriers gradually weakens, resulting in the gradual disappearance of the crystal phase structure of the catalyst, which is consistent with the analysis results of the pyrolysis experiment. Therefore, the Ni-Fe / 60%ASA@HZSM-5 catalyst has the same activity as the Ni-Fe / HZSM-5 catalyst and has the best catalytic activity.

[0086] (5) Therefore, the nitrogen adsorption-desorption isotherm and pore distribution of the Ni-Fe / ASA@HZSM-5 catalyst with an ASA content of 60% were analyzed, and the results are shown in Table 3.

[0087] Table 3

[0088]

[0089] It can be seen from Table 3 that compared with the Ni-Fe / HZSM-5 catalyst, the structural characteristics of the Ni-Fe / 60%ASA@HZ-5 catalyst are better, which once again shows that when ASA replaces 60% of the HZSM-5 molecular sieve and is used as a co-carrier to prepare the Ni-Fe / ASA@HZSM-5 catalyst, it has better catalytic activity, which is consistent with the XRD analysis results.

[0090] (6) Quantitative fitting analysis of the acid content of different Ni-Fe / ASA@HZSM-5 catalysts is shown in Table 4.

[0091] Table 4

[0092]

[0093] It can be seen that the weak acid, strong acid and total acid contents of the Ni-Fe / 20% ASA@HZ-5 catalyst are 0.10mmoL / g, 0.02mmoL / g and 0.13mmoL / g, respectively, which decrease by 80.8%, 41.2% and 84.9%, respectively; this indicates that the acid strength of the Ni-Fe catalyst is significantly reduced after adding 20% ​​ASA.

[0094] However, as the ASA addition ratio increased to 40% and 60%, the low-temperature peaks at 100-200°C moved to the high-temperature zone (143.9°C, 159.7°C), and the strong acid position at 230-650°C also moved to the high-temperature zone (549.9°C, 616.6°C), indicating that with the increase of ASA amount, the acid strength of Ni-Fe bimetallic catalyst increased. However, compared with the Ni-Fe / HZSM-5 catalyst, the peak area in the 100-200°C region decreased by 54.7% and 34.6%, respectively, and the weak acid content decreased by 53.5% and 26.7%, respectively; the peak area in the 230-650°C region decreased by 82.6% and 82.1%, respectively, and the strong acid content decreased by 88.2% and 91.2%, respectively, which resulted in a lower total acid content (0.40mmoL / g and 0.63mmoL / g, respectively); this is because with the increase of ASA addition, the coverage of the active metal surface increases, the total acid content decreases, and the strong acid content decreases significantly. At the same time, since ASA contains many metal oxides, such as copper, whose electronegativity is much higher than nickel, the metal species and the HZSM-5 molecular sieve are increased. The interaction of acid H atoms leads to the aggregation of copper atoms and the reduction of strong acid centers. In addition, the presence of Fe2O3 increases the cumulative electronegativity of iron, which leads to the aggregation of iron atoms and the reduction of acid centers. At the same time, the appropriate amount of ASA provides the catalyst with a higher weak Lewis acid site, creating suitable conditions for the cracking of aromatics.

[0095] Therefore, although the acidity of the catalyst prepared after ASA replaced HZSM-5 decreased; however, from the perspective of overall catalytic activity, the catalyst prepared after 60% ASA replaced HZSM-5 had a higher acidity and had a certain degree of catalytic activity.

[0096] More importantly, in terms of economy, according to the commercial price of HZSM-5 of 0.6 yuan / g, 1g of catalyst mixed carrier contains 0.6g of ASA and 0.4g of HZSM-5, then the cost of catalyst preparation can be reduced by 60%, which has good economic benefits and plays a role in saving costs; in terms of environment, ASA is a waste resource, and after activation, it can be used as a catalyst carrier to realize the reuse of waste resources, accelerate the process of ecological civilization construction, improve the non-point source pollution caused by improper disposal of urban and rural organic solid waste, and promote the construction of a "zero-waste society".

[0097] Therefore, it is feasible to replace HZSM-5 molecular sieve with ASA and co-load Ni-Fe catalyst, among which Ni-Fe / 60%ASA@HZSM-5 catalyst has the best performance, hereinafter collectively referred to as Ni-Fe / ASA@HZSM-5.

[0098] Example 3

[0099] Regeneration of Ni-Fe / ASA@HZSM-5 catalyst:

[0100] The catalyst was regenerated by calcination regeneration method, the calcination temperature was 600℃, and the calcination time was 3h. The regenerated catalyst participated in the next round of toluene cracking experiment to investigate the effect of the number of cycles of Ni-Fe / ASA@HZSM-5 catalyst for toluene pyrolysis on the catalytic activity. The results of the mass change, gas release rate and product distribution law of the catalyst after reaction and regeneration are as follows: Figure 3 .

[0101] Depend on Figure 3 (a) It can be seen that the amount of catalyst increases after each reaction, indicating that a certain amount of carbon deposits are produced after the pyrolysis of toluene; at the same time, the mass of the catalyst after each regeneration is higher than the original mass, indicating that the catalyst is collected more completely each time, the catalyst loss is small, and the data is available. The mass of the catalyst after the first regeneration is 0.077g less than the original mass, because this type of catalyst has a good effect of eliminating carbon deposits and a controllable error;

[0102] After the 2nd, 3rd and 4th regenerations, the mass of the catalyst increased by 0.0.12g, 0.34g and 0.43g respectively. These mass increases are permanent carbon deposits that cannot be eliminated by calcination. They will cause permanent deactivation of some active sites of the catalyst and are the main reason for the deterioration of catalyst activity and stability.

[0103] Combination Figure 3 (b) It can be seen that with the increase in the number of cycles, the release rates of the main gases (H2, CH4) have the same trend and show a significant downward trend; the toluene conversion rate does not change much in the four cycle experiments, but the gas and liquid yields gradually decrease and the solid yield gradually increases ( Figure 3 (c)), further indicating that the increase in catalyst mass with the increase in the number of cycles is permanent carbon deposition. Overall, the Ni-Fe / ASA@HZSM-5 catalyst prepared by ASA replacing part of the HZSM-5 molecular sieve and serving as a co-carrier has good catalytic activity and stability.

[0104] Example 4

[0105] Effect of catalyst amount on toluene pyrolysis characteristics:

[0106] The mass ratios of Ni-Fe / ASAHZSM-5 catalyst to toluene were 4%, 12%, 16%, and 20%, respectively. Toluene was catalyzed to produce gas at 800℃ in a nitrogen atmosphere in a two-stage fixed-bed reactor. The distribution of cracking products and the change of gas release rate are shown in the following results. Figure 4 .

[0107] from Figure 4(a) and (b) show that as the amount of catalyst increases from 4% to 16%, the release rates of the main gases (H2, CH4, CO, CO2) all show a significant increase trend and are clearly distinguished, indicating that the experiment went smoothly, the data was reliable, and the repeatability was good. The Ni-Fe / ASA@HZSM-5 catalyst can significantly promote the pyrolysis of toluene to produce gas. In particular, when the amount of catalyst is 16%, the release rates of H2, CH4, and CO2 are the largest, which are 27.10mL / min, 47.76mL / min, and 13.81mL / min, respectively; the time for the maximum rate of CO release is delayed to 15min (8.93mL / min), indicating that the appropriate amount of catalyst provides sufficient oxygen source for the reaction system, prolongs the oxygen release time of the catalyst, and provides conditions for the formation of the CO non-polar skeleton of the aromatic hydrocarbon and alkane derivative functional group, and obtains the highest gas yield (70.78%) and the lowest solid yield (0.11%) ( Figure 4 (c)), the carbon deposit amount relative to the catalyst is 152 mg / g -catalyst The total gas yield reached the maximum (113.95mL / g- toluene )( Figure 4 (d)), where the H2 yield increased to 40.66 mL / g- toluene , CO yield increased to 5.09mL / g, CO2 yield increased to 4.69mL / g- toluene , the CH4 yield does not change much; this indicates that sufficient Ni-Fe / ASA@HZSM-5 not only strengthens the hydrogen production pathway of toluene pyrolysis, but also promotes the carbon deposition gasification reaction (C+CO2=2CO), playing a dual role in increasing the H2 and CO yields.

[0108] When the amount of catalyst continued to increase to 20%, the release rates of the main gases (H2, CH4, CO, CO2) all decreased significantly. This is because too much Ni-Fe / ASAHZSM-5 leads to heat accumulation, which reduces the heat transfer rate and causes toluene molecules to accumulate on the surface of the solid heat carrier, resulting in a higher solid yield (0.61%) and a lower gas yield (92.67 mL / g- toluene ).

[0109] Therefore, the addition of catalyst promoted the pyrolysis of toluene to produce hydrogen and the gasification of carbon deposits, which significantly increased the gas yield; however, too much catalyst would also affect the heat and mass transfer rate and the pyrolysis process. Within the experimental investigation range, when the amount of catalyst was 16% relative to the mass of toluene, the best catalytic pyrolysis effect and directional pyrolysis hydrogen production pathway were shown.

[0110] The liquid products produced during biomass pyrolysis are complex mixtures of various organic compounds, and the amount of catalyst has a great influence on the product distribution. Therefore, the appropriate amount of catalyst is a prerequisite for ensuring the complete cracking and gasification of toluene. The developed Ni-Fe / ASAHZSM-5 catalyst can provide effective active centers for the cracking and deoxygenation of volatiles through a series of catalytic reactions.

[0111] Example 5

[0112] Effect of pyrolysis temperature on the pyrolysis performance of toluene:

[0113] In the catalytic cracking reaction, the cracking reaction of hydrocarbons includes cracking, reforming and condensation reactions, which are endothermic reactions. Increasing the temperature is conducive to the movement of the reaction equilibrium toward the product direction, promoting cracking and gas production; but too high a reaction temperature will cause the catalyst to sinter, reduce its activity, and cause serious carbon deposition.

[0114] Therefore, in order to explore the pyrolysis path of toluene catalyzed by Ni-Fe / ASA@HZSM-5 catalyst, the SEM images of toluene catalyzed by the catalyst at BUT reforming temperature (700-900℃) were studied in a secondary fixed bed reactor under the condition of constant carrier gas flow rate and cracking temperature of 600℃.

[0115] Depend on Figure 5 It can be seen that the morphology of the semi-coke formed after toluene pyrolysis at different temperatures is basically similar to that of the catalyst after the reaction, but the semi-coke yield and distribution density are significantly different. Figure 5 (a) Figure 5 (b) Compared with the fresh catalyst, the catalyst morphology after pyrolysis at 700℃ shows obvious pore structure. This is because the synergistic effect between the carriers and the active components promotes the complete pyrolysis of the light components at this temperature, and the carbon deposition is not obvious; see Figure 5 (c) When the temperature rises to 800°C, randomly dispersed spherical carbon particles are clearly visible on the catalyst surface and are irregularly distributed on the catalyst surface; however, obvious pore structures are still visible. This is because the increase in temperature promotes the polymerization reaction between toluene and its derivatives while promoting the cracking of toluene to produce gas, thus forming spherical carbon deposits; see Figure 5 (d), but when the temperature reaches 900℃, a large number of spherical particles can be seen on the catalyst surface and in the pores, and they grow in a fibrous form, and the pore structure of the catalyst is no longer clear. Therefore, if you want to obtain a higher conversion rate and gas production rate, you can appropriately increase the reaction temperature; within the experimental conditions, the pyrolysis effect of toluene is best when the pyrolysis temperature is 800℃.

[0116] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A method for preparing a multifunctional catalyst of aluminum ash and HZSM-5 molecular sieve co-supporting active metals, characterized in that: include, The activated aluminum ash and the molecular sieve are mechanically mixed uniformly to obtain an aluminum ash-molecular sieve co-carrier; After mixing the active metal precursor and the co-carrier, a dispersant is added to load the active metal on the co-carrier, and a solid is obtained after removing excess dispersant; The obtained solid is calcined in an inert atmosphere to obtain an aluminum ash-molecular sieve co-supported active metal catalyst; Wherein, the active metal precursor includes one or more of nickel nitrate, iron nitrate, magnesium nitrate, cerium nitrate, calcium nitrate, and cobalt nitrate; The dispersant includes deionized water and ethanol; The mass percentage of the active metal relative to the co-carrier is 1 to 8 wt.%; The activated aluminum ash accounts for 20% to 80% of the mass of the molecular sieve.

2. The preparation method according to claim 1, characterized in that: The preparation method of the activated aluminum ash includes hydrothermal activation and acid activation; Wherein, the hydrothermal activation temperature is 140-200°C, and the activation time is 2-4h; Wherein, the acid-activated preparation method comprises: After the aluminum ash slag is passed through a 80-100 mesh sieve, it is calcined at 600-800°C for 2-3 hours to obtain calcined aluminum ash; The calcined aluminum ash is added into the acid solution, stirred evenly, ultrasonically impregnated, centrifuged, the supernatant is poured out, the acidified aluminum slag is placed in a muffle furnace for high temperature roasting at 600°C for 3 hours, and taken out after natural cooling to obtain acid-activated aluminum ash.

3. The preparation method according to claim 1 or 2, characterized in that: The acid solution includes sulfuric acid, acetic acid and phosphoric acid, and the acid concentration is 1-7 mol / L.

4. The preparation method according to claim 1, characterized in that: The preparation method of the molecular sieve comprises: The molecular sieve raw material was ground and passed through an 80-mesh sieve, placed in a muffle furnace and heated to 550°C at a heating rate of 20°C / min, and calcined for 3 h; The molecular sieve raw material includes HZSM-5 zeolite molecular sieve.

5. The preparation method according to claim 1, characterized in that: The active metal is loaded on a common carrier, and the loading method includes an ultrasonic-assisted method, a microwave-assisted method, and an ion exchange method.

6. The preparation method according to claim 5, characterized in that: In the ultrasonic-assisted method, the ultrasonic treatment power is 60 to 80 W and the treatment time is 20 to 30 minutes.

7. The preparation method according to claim 1 or 6, characterized in that: The solid is obtained after removing the excess dispersant, wherein the removal method includes drying method and natural volatilization method.

8. The preparation method according to claim 1, characterized in that: The calcination is carried out in an inert atmosphere, wherein the calcination temperature is 500-600° C. and the calcination time is 3-4 hours.

9. The method according to any one of claims 1, 2, 4, 5, 6 or 8, characterized in that: The aluminum ash cooperates with the molecular sieve to co-carry an active metal catalyst, wherein the active metal includes metal Fe and metal Ni, the mass percentage of metal Fe relative to the co-carrier is 1-4wt.%, and the mass percentage of metal Ni relative to the co-carrier is 4-8wt.%.

10. Use of aluminum ash prepared by the preparation method according to any one of claims 1 to 9 in conjunction with molecular sieve co-supported nickel-iron catalyst in catalytic tar cracking to prepare hydrogen-rich fuel gas.

Citation Information

Cited By

  • Composite molecular sieve catalyst, preparation method and application thereof

    CN121648967A